As mulheres e o Geoparque Caçapava Aspirante Unesco: uma relação alinhavada pelo artesanato - Silva, Elisângela Lopes da (2022)
This thesis aims to understand how women artisans from Caçapava do Sul interact with the Caçapava Aspiring UNESCO Geopark and how it has contributed to the production of geoproducts and female empowerment. The methodological procedures involved qualitative-phenomenological research, based on the artisans' life stories. This procedure involved: (1) knowing the handicraft women community and its relationship with the artisanal know-how; (2) understanding the interaction of artisans with the tourist development of the municipality; and (3) understanding the role of the Caçapava Aspiring UNESCO Geopark in the life of these women. The results obtained in this thesis were divided into three thematic axes: a) women's life trajectory and their artisanal know-how, where it was identified that the relationship of artisans with the handicraft activity was mainly due to family obligations and needs to increase financial resources; b) the relationship of the artisans with the tourist issues of the territory, where it was possible to understand that the interaction of this public with the tourist sector is something recent, but that it has been contributing significantly to the development of new products and commercialization, as well as stimulating the participation of artisans in discussion spaces about the tourist potential in the municipality; c) the Caçapava Aspiring UNESCO Geopark as a driver of the empowerment of artisans, where it was identified that the activities and training offered by the Geopark have been stimulating women empowerment through the appreciation and visibility of these artisans. This process resulted in the empowerment and understanding of the need to organize themselves and their community as protagonists of the economic development. In addition, they were encouraged to develop geoproducts with territorial identity, allowing a more diversified and qualified offer of handicrafts to tourists visiting Caçapava do Sul. The development of geoproducts contributes to the generation of employment and income, both in the food production and in the handicraft sector and tourism services in various UNESCO Global Geoparks and it can represent an important source of autonomy and income for artisans. Geoproducts contribute to the financial independence of women, in the appreciation and visibility from the collective point of view of the interviewed artisans. The results obtained by this research demonstrate the importance of the involvement of women artisans in local development and, mainly, in the search for gender equality and female empowerment, being a strategic issue in the certification of a territory as UNESCO Global Geopark and in the achievement of SDG No. 5.